2009
DOI: 10.1002/nav.20332
|View full text |Cite
|
Sign up to set email alerts
|

Inventory policies for a make‐to‐order system with a perishable component and fixed ordering cost

Abstract: Abstract:We consider a make-to-order production system where two major components, one nonperishable (referred to as part 1) and one perishable (part 2), are needed to fulfill a customer order. In each period, replenishment decisions for both parts need to be made jointly before demand is realized and a fixed ordering cost is incurred for the nonperishable part. We show that a simple (s n , S 1 n , S 2 n ) policy is optimal. Under this policy, S 2 n along with the number of backorders at the beginning of a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…With respect to the inventory models with uncertain demand and shortages, nearly all of the authors assumed that all of the excess demand during the stock-out period become either lost sales [8, 51, 66, 68, 70, 73, 90, 98, 272, 273, 275, 276, 278, 281, 282, 288-290, 294, 296-300, 302, 303, 306, 309-311, 313, 316, 320-322, 326, 332, 335, 337-340], or shortages that are fully backlogged [8,35,112,278,284,286,287,295,297,308,315,319,321,323,325,329,341,343,347]. However, some models with uncertain demand consider a partial backlogging rate: [305,330,331,333] assume that a fixed fraction of shortages are backlogged while [328,342] assume a waiting time function for unmet demand.…”
Section: Inventory Models Including a Stock-out Periodmentioning
confidence: 99%
See 3 more Smart Citations
“…With respect to the inventory models with uncertain demand and shortages, nearly all of the authors assumed that all of the excess demand during the stock-out period become either lost sales [8, 51, 66, 68, 70, 73, 90, 98, 272, 273, 275, 276, 278, 281, 282, 288-290, 294, 296-300, 302, 303, 306, 309-311, 313, 316, 320-322, 326, 332, 335, 337-340], or shortages that are fully backlogged [8,35,112,278,284,286,287,295,297,308,315,319,321,323,325,329,341,343,347]. However, some models with uncertain demand consider a partial backlogging rate: [305,330,331,333] assume that a fixed fraction of shortages are backlogged while [328,342] assume a waiting time function for unmet demand.…”
Section: Inventory Models Including a Stock-out Periodmentioning
confidence: 99%
“…Although in most inventory systems the assumption of a single item is not real, very few studies have been found in the literature dealing with multi-item inventory control compared to single-item models. Two or more items in combination with shortages are taken into account in [34,35,70,99,101,102,105,123,155,245,279,284,292,296,299,311,315,341]. Inventory models considering an optimal price decision and multiple items can be found in [62,223].…”
Section: Multi-item Inventory Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Frank et al. (2009) considered an assembly system in which one product has a finite lifetime and the other is nonperishable. Zhou et al.…”
Section: Literature Reviewmentioning
confidence: 99%